Thermal modeling for supporting firefighting and emergency response planning. Issue 1 (23rd June 2022) - Wan, Bryan; Parker, Trent; Wang, Qingsheng
Abstract: This literature review looks at the various types of approaches to industrial storage tank fires and evaluates how quantitative consequence analysis with thermal modeling may aid in the development of industrial site fire preplans and emergency response planning guidelines. Emergency response planners may employ the use of thermal contours on plot plans generated by available consequence modeling software. Such performance‐based approaches can effectively take into account the associated sociotechnical factors and site‐specific hazards. With these approaches, the planners can identify appropriate preventative actions and responses, such as the activation of cooling on adjacent equipment, as well as establishing safe approach/muster point distances from hazardous sources of thermal heat stress.